2016
DOI: 10.1177/0009922816645513
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Complementary and Alternative Medicine (CAM) Services in Freestanding US Children’s Hospitals

Abstract: Complementary and alternative medicine (CAM) use among US children in 2012 was 11.6%, and studies show CAM use as high as 76% in certain pediatric populations. Children's hospitals offer varied CAM services. This survey aimed to identify CAM services offered, the structure of CAM departments, and supplement use policies in freestanding US children's hospitals. In our survey, 92% of responding children's hospitals offered CAM services, and 38% had hospital-based CAM centers; 60% of responders had policies for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…High rates of CAM use have been reported among children with chronic health conditions and children treated in outpatient settings, with some pediatric hospitals making CAM services available. 5 7 , 15 Most of the published surveys investigating the use of CAM in children have been performed in patients suffering from cancer, chronic gastrointestinal conditions, rheumatologic conditions, and neuropsychologic diseases. 16 20 Among children requiring surgery, the use of CAM in the perioperative period is less well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High rates of CAM use have been reported among children with chronic health conditions and children treated in outpatient settings, with some pediatric hospitals making CAM services available. 5 7 , 15 Most of the published surveys investigating the use of CAM in children have been performed in patients suffering from cancer, chronic gastrointestinal conditions, rheumatologic conditions, and neuropsychologic diseases. 16 20 Among children requiring surgery, the use of CAM in the perioperative period is less well understood.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Eighty-six percent of hospitals with Accreditation Council for Graduate Medical Education (ACGME)-approved pediatric anesthesia fellowship programs provided CAM therapies for pediatric pain management, while music therapy, acupuncture, and hypnotherapy were offered in 81%, 46%, and 38% of the freestanding US children’s hospitals, respectively. 5 , 22 With caregivers’ consent being integral to the perioperative use of CAM, we investigated knowledge and acceptance of CAM modalities as alternatives to anxiolytic premedication among caregivers of children presenting for surgery at a large tertiary care pediatric hospital. 4 Music therapy was the most accepted CAM method, and familiarity with this CAM modality was the only factor independently associated with the caregivers’ acceptance of CAM in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study addresses several gaps in the literature with regard to the provision of IM in US hospitals, as IM referral processes within an inpatient setting have not been studied previously. Although IM is increasingly being provided to US inpatients in areas such as oncology 14 15 and paediatrics, 16 17 hospitals with well-established IM offerings for inpatients are more prevalent internationally (eg, in Israel, 18 19 Germany 20 21 and China 22 ). However, operational processes and cultural contexts surrounding acceptance of IM are substantially different internationally in comparison with the USA, where IM offerings are less widespread and assimilated.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, a survey of freestanding children’s hospitals in the United States indicated that 96% of pediatric hospitals offer CAM services to hospitalized children. 1 Commonly offered complementary services in children’s hospitals include music therapy, acupuncture, guided imagery, clinical hypnotherapy, meditation, and pet therapy. These modalities are used to create a sense of relaxation, lessen stress, decrease nausea and pain, reduce procedural discomfort, and improve well-being.…”
Section: Introductionmentioning
confidence: 99%